2019
DOI: 10.1016/j.rboe.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Enxerto espesso versus técnica de duplo feixe na reconstrução do ligamento cruzado posterior: Estudo experimental biomecânico com cadáveres

Abstract: Objective  To evaluate the biomechanical effect of graft thickness compared with the double-bundle technique on posterior cruciate ligament (PCL) reconstruction in human cadaveric knees. Methods  A total of 9 human cadaveric knees were tested in 5 conditions: intact knee (INT); single-bundle reconstruction with a 10-mm quadriceps tendon (SB); double-bundle reconstruction with a 10 mm-quadriceps tendon for the anterolateral bundle and a 7-mm doubled semitendinosus tendon for the posteromedial bundle (DB); sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In PCL reconstruction surgery, the literature referring to the advantages of some reconstructive technique over another is very poor, however in a systematic review in cadaver studies, Lee et al [62] found that the double bundle gives more posterior stability than a one bundle. Maradei‐et al [69] found that the technique of a one bundle with a thick graft is superior to the double bundle. Xu et al [124] in a prospective comparative study in 59 patients, found no differences between the two techniques.…”
Section: Controversies In Diagnosis and Treatmentmentioning
confidence: 99%
“…In PCL reconstruction surgery, the literature referring to the advantages of some reconstructive technique over another is very poor, however in a systematic review in cadaver studies, Lee et al [62] found that the double bundle gives more posterior stability than a one bundle. Maradei‐et al [69] found that the technique of a one bundle with a thick graft is superior to the double bundle. Xu et al [124] in a prospective comparative study in 59 patients, found no differences between the two techniques.…”
Section: Controversies In Diagnosis and Treatmentmentioning
confidence: 99%